Grazing effects on biological soil crusts and their interaction with shrubs and grasses in an arid rangeland - Tabeni, Maria Solana (2014)
Question: Biological soil crust (BSC) communities can be used in the identification and monitoring of degradation. A key question is how landscape-scale livestock disturbance and other local-scale factors influence BSC communities. We hypothesize that at the landscape scale, increased grazing pressure would lead to decreasing cover of BSC, but at the local scale biotic interactions between BSC and vascular plants would modulate the influence of grazing on BSC. Methods: Spatially explicit sampling of vegetation composition and cover was conducted using point-sampling methods in digital images along two disturbance gradients in the central Monte Desert in Argentina. Results: The grazing gradient is the major determinant of changes in the structure of plant communities at the landscape scale. Approximately 1500 to 2000 m from a watering point, there is a threshold in vegetation structure associated with a nonlinear trend of the BSC, herb, grass and shrub cover. Bivariate spatial patterns show attraction between BSC and shrubs in the vicinity of settlements, and repulsion between BSC and both grasses and litter in less disturbed sites. Conclusion: Grazing affects BSC directly through trampling and indirectly by altering vascular plant communities that interact with the BSC communities. Both these effects vary according to the spatial scale being considered. The results evidence that understanding of livestock impact in structuring arid ecosystems requires an integrated analysis of BSC and vascular plant communities at different spatial scales.